PELAKSANAAN INSTRUKSIONAL MOTIVASI ARCS DESAIN MODEL UNTUK MENINGKATKAN DUKUNGAN BELAJAR SISWA BELAJAR JAUH - Benny Agus Pribadi; Asnah Marlina Limbong; Mohammad Firman Karim; Kadarisman Kadarisman (Akademika, 2021)
This study aims to elaborate the use of an instructional design model to enhance the effectiveness of conducting face-to-face students' learning support in the distance education system. Universitas Terbuka (UT) provides various learning supports for its students. The students can use both online and face-to-face tutorial programs to improve their learning process. UT must find the appropriate instructional strategy that enables to enhance students’ motivation in learning. One of the instructional design models that focus on the effort of improving students’ motivation in learning is the ARCS, motivational instructional design model. This model entails essential components that will support the process of learning such as Attention, Relevance, Confidence, and Satisfaction. The study involved 32 distant education students who participated in a face-to-face tutorial program. A pre and post-test session was conducted to get information regarding the impact of using the ARCS instructional design model to facilitate students’ learning. This research has implications for educators or trainers related to designing learning scenarios or developing learning design models.